Literasi Digital: Dampak Penggunaan AI terhadap Kesehatan Mental Remaja di Kota Kendari - Muh. Ihsan Zulfikar; Haekal Febriansyah Ramadhan; Ayu Hasnining; Mushaf Mushaf; Yasdin Yasdin (Universitas Negeri Makassar, 2026)
Abstract. The development of artificial intelligence (AI) technology has transformed the way adolescents learn, interact, and access information, while also presenting both opportunities and challenges for their mental health. The introduction of Coding and Artificial Intelligence as subjects in the national curriculum has further increased adolescents’ exposure to AI. This community service program aimed to enhance digital literacy among adolescents in Kendari City, particularly their understanding of healthy AI use and its relationship with mental health. The implementation consisted of three stages: preparation, implementation through digital literacy socialization and training, and evaluation. The target participants were 45 secondary school students. The level of achievement was measured using pre-test and post-test assessments of participants’ understanding, which were analyzed descriptively and through a paired-samples t-test. The results showed an improvement in participants’ understanding, with the mean score increasing from 56 on the pre-test to 84 on the post-test (on a 100-point scale), and this increase was statistically significant. The program successfully raised adolescents’ awareness of using AI wisely, enabling technology to support rather than disrupt their mental health. The activity was conducted with the support of Forum Anak Sulawesi Tenggara as a community partner.Keywords: digital literacy; artificial intelligence; mental health; adolescents; Kendari